Vicarious interaction: The role of observed online communication in fostering organization-public relationships. Issue 3 (25th May 2018) - Lee, Nicole; Seltzer, Trent
Abstract : Purpose: The purpose of this paper is to explore how online interaction with an organization impacts not only those users participating in the exchange, but also those that witness the interaction and are influenced as suggested by social cognitive theory. Design/methodology/approach: This study utilized a mixed methodological approach. First, 20 interviews with social media users were conducted to explore their perceptions of observed two-way communication between organizations and other users within social media spaces. An experiment then compared the effects of interacting with an organization via social media vs simply observing organizations interacting with other users. Findings: The findings from both studies support the assertion that publics do not have to actively participate in two-way communication with an organization for an observed exchange to have an impact. When an organization has a conversation with one follower, others see that interaction and are affected by it. Practical implications: This study has implications for the practice of online communication by organizations. Practitioners must consider how interactions impact those publics who are observing rather than only the few who are engaging. In the social media realm, priority should be given to followers posting legitimate questions or concerns. Responding to positive comments can also improve perceptions of the organization but is seen as going above and beyond. Originality/value: This paper introduces the concept of vicarious interaction – a phenomenon warranting further investigation by strategic communication scholars. Distinguishing between the effects of "vicarious interaction" and direct interaction could have significant consequences for the study of relational or symmetrical approaches to social media.